2019
DOI: 10.1016/j.cll.2019.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Direct-from-Specimen Pathogen Identification

Abstract: KEYWORDS Syndromic panel Respiratory panel Sepsis panel Gastroenteritis panel Meningitis panel Encephalitis panel KEY POINTSSyndromic panels should evolve to include additional pathogen targets.Syndromic panels should be flexible in design to better meet the user's needs.Syndromic panels should include host response markers to correlate with pathogen detection. Syndromic panels should have shorter run times, less complexity, and be placed near the point of care. Syndromic panels should be expanded to include m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Syndromic Panels "Syndromic panel" is a term commonly used in clinical microbiology when referring to rapid, multiplexed amplification and detection platforms that received US FDA approval or clearance for a set list of targets in a specific sample type [6]. This includes panels for gastrointestinal, central nervous system and respiratory tract infection-associated potential pathogens.…”
Section: Rapid Molecular Testingmentioning
confidence: 99%
See 3 more Smart Citations
“…Syndromic Panels "Syndromic panel" is a term commonly used in clinical microbiology when referring to rapid, multiplexed amplification and detection platforms that received US FDA approval or clearance for a set list of targets in a specific sample type [6]. This includes panels for gastrointestinal, central nervous system and respiratory tract infection-associated potential pathogens.…”
Section: Rapid Molecular Testingmentioning
confidence: 99%
“…For a detailed review of individual respiratory tract rapid syndromic respiratory panels, readers are referred to the following references (6,8). While individual targets vary, in general, these panels contain most known, widely circulating respiratory viruses and a limited set of atypical upper respiratory tract bacterial targets.…”
Section: Respiratory Tract Infection Syndromic Panelsmentioning
confidence: 99%
See 2 more Smart Citations
“…So how are upper respiratory syndromic panels affecting patient care? Results are mixed, with some studies showing a decrease in antibiotic therapy, decreased length of hospital stay, or decreased additional tests and imaging studies, 32 whereas other studies showed no benefit. 33 Many of the studies found benefits only for patients with positive influenza results, 34 , 35 showing that limited testing may be sufficient for most patients.…”
Section: Detection Of Upper Respiratory Infectionmentioning
confidence: 99%